Pulmonary sarcoid-like granulomatosis induced by aluminum dust: A case report and literature review - Du, Xuqin; Song, Lihong; Feng, Ruie; Ye, Qiao (Frontiers in Medicine, 2023)
Case report: We present a case of a 48-year-old woman with 27 months of exposure to aluminum dust and silica owing to polishing processing. The patient was admitted to our hospital with intermittent cough and expectoration. Chest high-resolution computed tomography showed diffuse ill-defined centrilobular nodules as well as patchy ground-glass opacities in bilateral lungs. A video-assisted thoracoscopic surgery biopsy demonstrated multiple isolated and confluent granulomas in an otherwise normal parenchyma without malignancy or signs of infection. Elemental analysis was performed on the grinding wheel powder in the workplace using an X-ray fluorescence spectrometric analyzer, showing 72.7% of Al2O3 and 22.8% of SiO2 as the raw materials. [The results of the mineralogical analysis has been added in the abstract (Line 31-33). ]She was diagnosed with aluminum-associated sarcoid-like granulomatous lung disease, rather than sarcoidosis, according to occupational exposure by a multidisciplinary panel. Conclusion: Occupational aluminum dust exposure may induce pulmonary sarcoid-like granulomatosis recognized by a multidisciplinary diagnostic panel.